Pelvic packing or endovascular interventions: Which should be given priority in managing hemodynamically unstable pelvic fractures? A systematic review and a meta-analysis - Dong Zhang, MD; Gong-zi Zhang, MD; Ye Peng, MD; Shu-wei Zhang, MD; Meng Li, MD; Yv Jiang, MD; Lihai Zhang, MD (Surgery Open Science, 2024)
Background: Pelvic fractures in trauma patients can be associated with substantial massive hemorrhage. Hemostasis interventions mainly consist of pelvic packing (PP) and endovascular intervention (EI), such as angiography-embolization (AE) and resuscitative endovascular balloon occlusion of the aorta (REBOA). Whether PP or EI should be prioritized for the management of hemodynamic unstable patients with pelvic fractures remains under debate. This meta-analysis aimed to establish the evidence-based recommendations for the management of hemodynamic unstable patients. Materials and methods: PubMed, CENTRAL, and EMBASE databases were searched for articles published from January 1, 2000 to January 31, 2023. Eligible studies, such as retrospective cohort studies, propensity score matching studies, prospective cohort studies, observational cohort studies, quasi-randomized clinical trials evaluating PP and EI (AE or REBOA) for the management of patients with hemodynamically unstable pelvic fractures, were included. Mean Difference (MD), relative risk (RR), and 95 % confidence intervals (CI) were calculated using fixed- or random-effects models depending on the heterogeneity of included trials. We compared the effectiveness of the two methods in terms of mortality, unstable fracture pattens, injury severity score (ISS), systolic blood pressure (SBP), lactate (LA), base deficiency (BE), hemoglobin preoperatively, blood transfusion requirement, the time to and of operation, complications. Results: Overall, 15 trials enrolling 1136 patients were analyzed, showing a total mortality rate of 28.4 % (323/1136). No effect of PP preference on the ISS (PP 36.4 ± 10.4 vs. EI 34.5 ± 12.7), SBP (PP 81.1 ± 24.3 mmHg vs. EI 94.2 ± 32.4 mmHg), LA (PP 4.66 ± 2.72 mmol/L vs. 4.85 ± 3.45 mmol/L), BE (PP 8.14 ± 5.64 mmol/L vs. 6.66 ± 5.68 mmol/L), and unstable fracture patterns (RR = 1.10, 95 % CI [0.63, 1.92]) was observed. PP application was associated with lower preoperative hemoglobin level (PP 8.11 ± 2.28 g/dL vs. EI 8.43 ± 2.43 g/dL, p < 0.05), more preoperative transfusion (MD = 2.53, 95 % CI [0.01, 5.06]), less postoperative transfusion within the first 24 h (MD = −1.09, 95 % CI [−1.96, −0.22]), shorter waiting time to intervention (MD = −0.93, 95 % CI [−1.54, −0.31]), and shorter operation time of intervention (MD = −0.41, 95 % CI [−0.52, −0.30]). PP had lower mortality rate owing to uncontrolled hemorrhage in the acute phase (RR = 0.41, 95 % CI [0.22, 0.79]). There was neither difference in mortality due to other complications (RR = 1.60, 95 % CI [0.79, 3.24]), nor in total mortality (RR = 0.92, 95%CI [0.49, 1.74]) (p > 0.05). Conclusions: PP showed advantages of reducing the amount of postoperative transfusion, shortening the time of waiting and operating, and decreasing mortality due to uncontrolled hemorrhage in the acute phase without raising the odds of mortality due to complications. PP, a reliable hemostatic method, should be prioritized for resuscitating most pelvic fractures with hemodynamically unstable, especially in case of bleeding from veins and fracture sites, as well as inadequate EI.